INNOVATIVE APPROACHES TO IMPROVING THE QUALITY OF SCIENCE, EDUCATION - Tolliboyev, Dilshod; Miyzamov, Zubaydulla (Science technology&Digital finance, 2023)
The article argues that the enormous discoveries that are being made in science today and their large-scale introduction to production should strengthen the role of scientists in social and economic life. An important link in large – scale reform-innovation today demonstrates its advantages in the educational system, as in every industry.